The Role of Cephalometry in The Diagnosis of Orthodontic Patients (Texas Journal of Medical Science, 2023)
Orthodontics is a department of dentistry that focuses on the alignment and positioning of enamel and jaws to acquire top of the line oral fitness and function. To supply high quality orthodontic treatment, correct prognosis is crucial. The use of cephalometry, a specialised imaging technique, performs a pivotal function in evaluating and diagnosing orthodontic patients. This article objectives to spotlight the importance of cephalometry in orthodontic diagnosis, showcasing its advantages and applications.